PECULIARITIES AND TYPES OF ORGANIZING EXTRACURRICULAR ACTIVITIES IN MATHEMATICS IN ELEMENTARY GRADES (Conferencea, 2023)
This article is about the specific features and types of organizing extracurricular activities in mathematics in elementary grades, it includes various methods, goals and objectives of organizing extracurricular activities in mathematics in elementary grades, types of extracurricular activities and information about their organizational features is given.